Statistical Study on the Impact of Computer-use on Child-health in the Arab-community - Nasser M. Al-Subaie Rahgad; Hamuwd A. Al-Subaie Hiafa; Turki M. Al-Subaie Dhabia; Mostafa M. Sabra Sherifa (Journal of Biotechnology and Biomedical Science, 2023)
United States of America (USA), Australia, and Canada recommending children computer-use should be imperfect. It obligated a strong influence on children’s lives. The problem was for stuck in the computer-use for a long time per day. The goal was to follow child-health in the Arab-community to notice its influence on the child-health. The method was through a arithmetical study by sending Internet questionnaire and receiving the parents' advice. The results were in the 500 parent answers and 14 comments. The first was
Keywords: Computer-use